Effects of soil salinity on rice production and technical efficiency: Evidence from the northern coastal region of Central Java, Indonesia - Renie Oelviani; Witono Adiyoga; Tota Suhendrata; I Gede Mahatma Yuda Bakti; Himawan Arif Sutanto; Diah Arina Fahmi; Chanifah Chanifah; Ratih Kurnia Jatuningtyas; Samijan Samijan; Afrizal Malik; Dewi Sahara; Budi Utomo; et al. (Case Studies in Chemical and Environmental Engineering)
Coastal rice production in Central Java, Indonesia, is hindered by elevated salinity levels. Salinity has an impact on the production of rice and the technical efficiency of farmers in the northern coastal region of Central Java. The Stochastic Frontier Analysis (SFA) model could distinguish the production function, technical efficiency, and inefficiency of rice farming on saline and non-saline soil. Environmental variables such as salinity level and rainfall greatly affect rice farming. The investigation employed data from 225 farmers growing both in saline and non-saline soil. Our investigation unveiled that soil salinity causes a decrease of 29.29 % in rice yield compared to non-salinity. The average technical efficiencies of rice production in saline only reach 73 %, while non-saline soil can reach 80 %. Inefficiency was significantly influenced by social factors such as farmers' age, education, and occupation. Experience and expertise assisted elderly farmers with salinity soil in improving their efficiency. The study emphasizes the importance of cultivating rice varieties with high salinity tolerance, improving irrigation infrastructure, and equipping farmers with up-to-date agricultural techniques. These treatments have the potential to enhance productivity and efficiency in areas that are impacted by salinity. It profoundly impacts Indonesia's strategy, and other nations encounter analogous challenges. Additional study is required to identify sustainable techniques for salinity management in rice agriculture across various locations.